On the longitudinal Vibrations of Tapered Bars - Chehil, D.S.; Dhaliwal, R.S. (Engineering Transactions, 1981)
In this paper an attempt is made to improve the elementary theory that describes the longitudinal vibrations of a tapered rod. The differential equation including both lateral inertia and shear is derived. In order to facilitate comparison with the known results, numerical values of the fundamental resonant frequencies and velocity gain factors are obtained for conical bars with linear taper.